Carbonised wooden objects and wood charcoal from an Iron Age feasting context in North-western Iberia: the case study of Frijão (Braga, Portugal) - Martín-Seijo, María (2015)
The site of Frijão in North-western Iberia was occupied during a period between the 4th and 2nd centuries BC and it is a very unique site in the context of the local Iron Age network. Its features suggest that it was a place to celebrate ceremonies related to feasting, in the same context 71 fragments of a riveted cauldron, seeds and fruits, burned bone, pottery and carbonised wooden manufactured pieces were found. These woodcrafts included a handle made of hazel wood (Corylus avellana), two fragments of one or more vessels of Rosaceae/Maloideae and four fragments of indeterminate objects made of oak (Quercus sp. deciduous) and alder buckthorn (Frangula alnus) wood. Other recoveries included fragments of oak charcoal interpreted as the charred remnants of a building made of perishable materials. The study of the archaeobotanical assemblages of Frijão highlighted the difficulties of interpreting the results of carbonised wood samples from fire-events – i.e. to distinguish between firewood and wooden manufactures – and the importance of registering dendrological and taphonomical data to go beyond taxonomical identification.